Dietary Reference Intakes for Vitamin A, Vitamin K, Arsenic, Boron, Chromium, Copper, Iodine, Iron, Manganese, Molybdenum, Nickel, Silicon, Vanadium, and Zinc - Institute of Medicine
This volume is the newest release in the authoritative series issued by the National Academy of Sciences on dietary reference intakes (DRIs). This series provides recommended intakes, such as Recommended Dietary Allowances (RDAs), for use in planning nutritionally adequate diets for individuals based on age and gender. In addition, a new reference intake, the Tolerable Upper Intake Level (UL), has also been established to assist an individual in knowing how much is \

Informing America's Policy on Illegal Drugs: What We Don't Know Keeps Hurting Us - National Research Council (The National Academies Press, 2001)
How should the war on drugs be fought? Everyone seems to agree that the United States ought to use a combination of several different approaches to combat the destructive effects of illegal drug use. Yet there is a remarkable paucity of data and research information that policy makers require if they are to create a useful, realistic policy package-details about drug use, drug market economics, and perhaps most importantly the impact of drug enforcement activities. Informing America's Policy on Illegal Drugs recommends ways to close these gaps in our understanding-by obtaining the necessary data on drug prices and consumption (quantity in addition to frequency); upgrading federal management of drug statistics; and improving our evaluation of prevention, interdiction, enforcement, and treatment efforts. The committee reviews what we do and do not know about illegal drugs and how data are assembled and used by federal agencies. The book explores the data and research information needed to support strong drug policy analysis, describes the best methods to use, explains how to avoid misleading conclusions, and outlines strategies for increasing access to data. Informing America's Policy on Illegal Drugs also discusses how researchers can incorporate randomization into studies of drug treatment and how state and local agencies can compare alternative approaches to drug enforcement. Charting a course toward a better-informed illegal drugs policy, this book will be important to federal and state policy makers, regulators, researchers, program administrators, enforcement officials, journalists, and advocates concerned about illegal drug use.

Dietary Reference Intakes: Proposed Definition of Dietary Fiber - Institute of Medicine (The National Academies Press, 2001)
The current situation regarding labeling and defining dietary fiber in the United States and many other countries is arbitrary due to its reliance on analytical methods as opposed to an accurate definition that includes its role in health. Without an accurate definition, compounds can be designed or isolated and concentrated using the currently available methods, without necessarily providing beneficial health effects. Other compounds can be developed that are nondigestible and provide beneficial health effects, yet do not meet the current U.S. definition based on analytical methods. For the above reasons, the Food and Nutrition Board, under the oversight of the Standing Committee on the Scientific Evaluation of Dietary Reference Intakes, assembled a Panel on the Definition of Dietary Fiber to develop a proposed definition(s) of dietary fiber. This Panel held three meetings and a workshop.

Clearing the Smoke: Assessing the Science Base for Tobacco Harm Reduction - Institute of Medicine
Despite overwhelming evidence of tobacco's harmful effects and pressure from anti-smoking advocates, current surveys show that about one-quarter of all adults in the United States are smokers. This audience is the target for a wave of tobacco products and pharmaceuticals that claim to preserve tobacco pleasure while reducing its toxic effects. Clearing the Smoke addresses the problems in evaluating whether such products actually do reduce the health risks of tobacco use. Within the context of regulating such products, the committee explores key questions: Does the use of such products decrease exposure to harmful substances in tobacco? Is decreased exposure associated with decreased harm to health? Are there surrogate indicators of harm that could be measured quickly enough for regulation of these products? What are the public health implications? This book looks at the types of products that could reduce harm and reviews the available evidence for their impact on various forms of cancer and other major ailments. It also recommends approaches to governing these products and tracking their public health effects. With an attitude of healthy skepticism, Clearing the Smoke will be important to health policy makers, public health officials, medical practitioners, manufacturers and marketers of \

Caffeine for the Sustainment of Mental Task Performance: Formulations for Military Operations - Institute of Medicine (The National Academies Press, 2001)
This report from the Committee on Military Nutrition Research reviews the history of caffeine usage, the metabolism of caffeine, and its physiological effects. The effects of caffeine on physical performance, cognitive function and alertness, and alleviation of sleep deprivation impairments are discussed in light of recent scientific literature. The impact of caffeine consumption on various aspects of health, including cardiovascular disease, reproduction, bone mineral density, and fluid homeostasis are reviewed. The behavioral effects of caffeine are also discussed, including the effect of caffeine on reaction to stress, withdrawal effects, and detrimental effects of high intakes. The amounts of caffeine found to enhance vigilance and reaction time consistently are reviewed and recommendations are made with respect to amounts of caffeine appropriate for maintaining alertness of military personnel during field operations. Recommendations are also provided on the need for appropriate labeling of caffeine-containing supplements, and education of military personnel on the use of these supplements. A brief review of some alternatives to caffeine is also provided.

Marijuana As Medicine?: The Science Beyond the Controversy - Institute of Medicine (The National Academies Press, 2001)
Some people suffer from chronic, debilitating disorders for which no conventional treatment brings relief. Can marijuana ease their symptoms? Would it be breaking the law to turn to marijuana as a medication? There are few sources of objective, scientifically sound advice for people in this situation. Most books about marijuana and medicine attempt to promote the views of advocates or opponents. To fill the gap between these extremes, authors Alison Mack and Janet Joy have extracted critical findings from a recent Institute of Medicine study on this important issue, interpreting them for a general audience. Marijuana As Medicine? provides patients2014as well as the people who care for them2014with a foundation for making decisions about their own health care. This empowering volume examines several key points, including: Whether marijuana can relieve a variety of symptoms, including pain, muscle spasticity, nausea, and appetite loss. The dangers of smoking marijuana, as well as the effects of its active chemical components on the immune system and on psychological health. The potential use of marijuana-based medications on symptoms of AIDS, cancer, multiple sclerosis, and several other specific disorders, in comparison with existing treatments. Marijuana As Medicine? introduces readers to the active compounds in marijuana. These include the principal ingredient in Marinol, a legal medication. The authors also discuss the prospects for developing other drugs derived from marijuana's active ingredients. In addition to providing an up-to-date review of the science behind the medical marijuana debate, Mack and Joy also answer common questions about the legal status of marijuana, explaining the conflict between state and federal law regarding its medical use. Intended primarily as an aid to patients and caregivers, this book objectively presents critical information so that it can be used to make responsible health care decisions. Marijuana As Medicine? will also be a valuable resource for policymakers, health care providers, patient counselors, medical faculty and students2014in short, anyone who wants to learn more about this important issue.

Innovation and Invention in Medical Devices: Workshop Summary - Institute of Medicine (The National Academies Press, 2001)
The objective of the workshop that is the subject of this summary report was to present the challenges and opportunities for medical devices as perceived by the key stakeholders in the field. The agenda, and hence the summaries of the presentations that were made in the workshop and which are presented in this summary report, was organized to first examine the nature of innovation in the field and the social and economic infrastructure that supports such innovation. The next objective was to identify and discuss the greatest unmet clinical needs, with a futuristic view of technologies that might meet those needs. And finally, consideration was given to the barriers to the application of new technologies to meet clinical needs.

Exploring the Biological Contributions to Human Health: Does Sex Matter? - Institute of Medicine (The National Academies Press, 2001)
It's obvious why only men develop prostate cancer and why only women get ovarian cancer. But it is not obvious why women are more likely to recover language ability after a stroke than men or why women are more apt to develop autoimmune diseases such as lupus. Sex differences in health throughout the lifespan have been documented. Exploring the Biological Contributions to Human Health begins to snap the pieces of the puzzle into place so that this knowledge can be used to improve health for both sexes. From behavior and cognition to metabolism and response to chemicals and infectious organisms, this book explores the health impact of sex (being male or female, according to reproductive organs and chromosomes) and gender (one's sense of self as male or female in society). Exploring the Biological Contributions to Human Health discusses basic biochemical differences in the cells of males and females and health variability between the sexes from conception throughout life. The book identifies key research needs and opportunities and addresses barriers to research. Exploring the Biological Contributions to Human Health will be important to health policy makers, basic, applied, and clinical researchers, educators, providers, and journalists-while being very accessible to interested lay readers.

Capitalizing on New Needs and New Opportunities: Government-Industry Partnerships in Biotechnology and Information Technologies - National Research Council (The National Academies Press, 2001)
This report addresses a topic of recognized policy concern. To capture the benefits of substantial U.S. investments in biomedical R&D, parallel investments in a wide range of seemingly unrelated disciplines are also required. This report summarizes a major conference that reviewed our nation's R&D support for biotechnology and information technologies. The volume includes newly commissioned research and makes recommendations and findings concerning the important relationship between information technologies and biotechnology. It emphasizes the fall off in R&D investments needed to sustain the growth of the U.S. economy and to capitalize on the growing investment in biomedicine. It also encourages greater support for inter-disciplinary training to support new areas such as bioinformatics and urges more emphasis on and support for multi-disciplinary research centers.

Multiple Sclerosis: Current Status and Strategies for the Future - Institute of Medicine (The National Academies Press, 2001)
Multiple sclerosis is a chronic and often disabling disease of the nervous system, affecting about 1 million people worldwide. Even though it has been known for over a hundred years, no cause or cure has yet been discovered2014but now there is hope. New therapies have been shown to slow the disease progress in some patients, and the pace of discoveries about the cellular machinery of the brain and spinal cord has accelerated. This book presents a comprehensive overview of multiple sclerosis today, as researchers seek to understand its processes, develop therapies that will slow or halt the disease and perhaps repair damage, offer relief for specific symptoms, and improve the abilities of MS patients to function in their daily lives. The panel reviews existing knowledge and identifies key research questions, focusing on: Research strategies that have the greatest potential to understand the biological mechanisms of recovery and to translate findings into specific strategies for therapy. How people adapt to MS and the research needed to improve the lives of people with MS. Management of disease symptoms (cognitive impairment, depression, spasticity, vision problems, and others). The committee also discusses ways to build and financially support the MS research enterprise, including a look at challenges inherent in designing clinical trials. This book will be important to MS researchers, research funders, health care advocates for MS research and treatment, and interested patients and their families.

No Time to Lose: Getting More from HIV Prevention - Institute of Medicine (The National Academies Press, 2001)
The United States has spent two productive decades implementing a variety of prevention programs. While these efforts have slowed the rate of infection, challenges remain. The United States must refocus its efforts to contain the spread of HIV and AIDS in a way that would prevent as many new HIV infections as possible. No Time to Lose presents the Institute of Medicine2019s framework for a national prevention strategy.

Firepower in the Lab: Automation in the Fight Against Infectious Diseases and Bioterrorism - Scott P. Layne; Tony J. Beugelsdijk; C. Kumar; N. Patel
Today's world poses a triple threat to the American population: infectious diseases, contamination of food and water, and bioattacks (biowarfare or bioterrorism). At least 17 countries are producing weapons of mass destruction using viruses, bacteria, or their toxins. AIDS, E. coli contamination, drug-resistant tuberculosis, and virulent flu strains are perhaps the best known of a host of disease threats. What these dangers have in common is the amount of data required to achieve solutions; in some cases, as much as a petabit (1 followed by 15 zeros) of data is required to study large numbers of samples from widespread locations. Firepower in the Lab examines how the nation can combat this triple threat by improving our ability to detect, measure, and monitor harmful biological agents. It explores the potential of today's exciting new laboratory automation and computer technologies as well as the emerging tools of molecular biology–how we can generate and analyze more data quickly and reduce human hands-on involvement, which inevitably introduces errors. The book discusses how to improve and apply technologies such as robotics, laboratory automation, \

Emerging Infectious Diseases from the Global to the Local Perspective: A Summary of a Workshop of the Forum on Emerging Infections - Institute of Medicine (The National Academies Press, 2001)
In October 1999, the Forum on Emerging Infections of the Institute of Medicine convened a two-day workshop titled 201cInternational Aspects of Emerging Infections.201d Key representatives from the international community explored the forces that drive emerging infectious diseases to prominence. Representatives from the Americas, Africa, Asia and the Pacific, and Europe made formal presentations and engaged in panel discussions. Emerging Infectious Diseases from the Global to the Local Perspective includes summaries of the formal presentations and suggests an agenda for future action. The topics addressed cover a wide range of issues, including trends in the incidence of infectious diseases around the world, descriptions of the wide variety of factors that contribute to the emergence and reemergence of these diseases, efforts to coordinate surveillance activities and responses within and across borders, and the resource, research, and international needs that remain to be addressed.

Food Safety Policy, Science, and Risk Assessment: Strengthening the Connection: Workshop Proceedings - Institute of Medicine
The Institute of Medicine's (IOM's) Food Forum was established in 1993 to allow science and technology leaders in the food industry, top administrators in several federal government agencies from the United States and Canada, representatives from consumer interest groups, and academicians to openly communicate in a neutral setting. The Food Forum provides a mechanism for these diverse groups to discuss food, food safety, and food technology issues and to identify possible approaches for addressing these issues by taking into consideration the often complex interactions among industry, regulatory agencies, consumers, and academia. The objective, however, is to illuminate issues, not to resolve them. Unlike study committees of the IOM, forums cannot provide advice or recommendations to any government agency or other organization. Similarly, workshop summaries or other products resulting from forum activities are precluded from reaching conclusions or recommendations but, instead, are intended to reflect the variety of opinions expressed by the participants. On July 13-14, 1999, the forum convened a workshop on Food Safety Policy, Science, and Risk Assessment: Strengthening the Connection. The purpose of the workshop was to address many of the issues that complicate the development of microbiological food safety policy, focusing on the use of science and risk assessment in establishing policy and in determining the utilization of food safety resources. The purpose was not to find fault with past food safety regulatory activities or food safety policy decisions. Rather, the goal was to determine what actions have been taken in the past to address food safety issues, to consider what influences led to the policies that were put in place, and to explore how improvements can be made in the future. This report is a summary of the workshop presentations. It is limited to the views and opinions of those invited to present at the workshop and reflects their concerns and areas of expertise. As such, the report does not provide a comprehensive review of the research and current status of food safety policy, science, and risk assessment. The organization of the report approximates the order of the presentations at the workshop. The identification of a speaker as an \

Standing Operating Procedures for Developing Acute Exposure Guideline Levels for Hazardous Chemicals - National Research Council (The National Academies Press, 2001)
Standing Operating Procedures for Developing Acute Exposure Guideline Levels for Hazardous Chemicals contains a detailed and comprehensive methodology for developing acute exposure guideline levels (AEGLs) for toxic substances from inhalation exposures. The book provides guidance on what documents and databases to use, toxicity endpoints that need to be evaluated, dosimetry corrections from animal to human exposures, selection of appropriate uncertainty factors to address the variability between animals and humans and within the human population, selection of modifying factors to address data deficiencies, time scaling, and quantitative cancer risk assessment. It also contains an example of a summary of a technical support document and an example of AEGL derivation. This book will be useful to persons in the derivation of levels from other exposure routes2014both oral and dermal2014as well as risk assessors in the government, academe, and private industry.

Classroom Assessment and the National Science Education Standards - National Research Council (The National Academies Press, 2001)
The National Science Education Standards address not only what students should learn about science but also how their learning should be assessed. How do we know what they know? This accompanying volume to the Standards focuses on a key kind of assessment: the evaluation that occurs regularly in the classroom, by the teacher and his or her students as interacting participants. As students conduct experiments, for example, the teacher circulates around the room and asks individuals about their findings, using the feedback to adjust lessons plans and take other actions to boost learning. Focusing on the teacher as the primary player in assessment, the book offers assessment guidelines and explores how they can be adapted to the individual classroom. It features examples, definitions, illustrative vignettes, and practical suggestions to help teachers obtain the greatest benefit from this daily evaluation and tailoring process. The volume discusses how classroom assessment differs from conventional testing and grading-and how it fits into the larger, comprehensive assessment system.

Knowing and Learning Mathematics for Teaching: Proceedings of a Workshop - National Research Council (The National Academies Press, 2001)
There are many questions about the mathematical preparation teachers need. Recent recommendations from a variety of sources state that reforming teacher preparation in postsecondary institutions is central in providing quality mathematics education to all students. The Mathematics Teacher Preparation Content Workshop examined this problem by considering two central questions: What is the mathematical knowledge teachers need to know in order to teach well? How can teachers develop the mathematical knowledge they need to teach well? The Workshop activities focused on using actual acts of teaching such as examining student work, designing tasks, or posing questions, as a medium for teacher learning. The Workshop proceedings, Knowing and Learning Mathematics for Teaching, is a collection of the papers presented, the activities, and plenary sessions that took place.

Improving Palliative Care for Cancer - Institute of Medicine; National Research Council (The National Academies Press, 2001)
In our society2019s aggressive pursuit of cures for cancer, we have neglected symptom control and comfort care. Less than one percent of the National Cancer Institute2019s budget is spent on any aspect of palliative care research or education, despite the half million people who die of cancer each year and the larger number living with cancer and its symptoms. Improving Palliative Care for Cancer examines the barriers2014scientific, policy, and social2014that keep those in need from getting good palliative care. It goes on to recommend public- and private-sector actions that would lead to the development of more effective palliative interventions; better information about currently used interventions; and greater knowledge about, and access to, palliative care for all those with cancer who would benefit from it.

Safe Passage: Astronaut Care for Exploration Missions - Institute of Medicine (The National Academies Press, 2001)
Safe Passage: Astronaut Care for Exploration Missions sets forth a vision for space medicine as it applies to deep space voyage. As space missions increase in duration from months to years and extend well beyond Earth's orbit, so will the attendant risks of working in these extreme and isolated environmental conditions. Hazards to astronaut health range from greater radiation exposure and loss of bone and muscle density to intensified psychological stress from living with others in a confined space. Going beyond the body of biomedical research, the report examines existing space medicine clinical and behavioral research and health care data and the policies attendant to them. It describes why not enough is known today about the dangers of prolonged travel to enable humans to venture into deep space in a safe and sane manner. The report makes a number of recommendations concerning NASA's structure for clinical and behavioral research, on the need for a comprehensive astronaut health care system and on an approach to communicating health and safety risks to astronauts, their families, and the public.

Occupational Health and Workplace Monitoring at Chemical Agent Disposal Facilities - National Research Council (The National Academies Press, 2001)
In keeping with a congressional mandate (Public Law 104-484) and the Chemical Weapons Convention, the United States is currently destroying its chemical weapons stockpile. The Army must ensure that the chemical demilitarization workforce is protected from the risks of exposure to hazardous chemicals during disposal operations and during and after facility closure. Good industrial practices developed in the chemical and nuclear energy industries and other operations that involve the processing of hazardous materials include workplace monitoring of hazardous species and a systematic occupational health program for monitoring workers' activities and health. In this report, the National Research Council Committee on Review and Evaluation of the Army Chemical Stockpile Disposal Program examines the methods and systems used at JACADS and TOCDF, the two operational facilities, to monitor the concentrations of airborne and condensed-phase chemical agents, agent breakdown products, and other substances of concern. The committee also reviews the occupational health programs at these sites, including their industrial hygiene and occupational medicine components. Finally, it evaluates the nature, quality, and utility of records of workplace chemical monitoring and occupational health programs.